2022
DOI: 10.1096/fj.202101307r
|View full text |Cite|
|
Sign up to set email alerts
|

Circular RNA circBFAR promotes glioblastoma progression by regulating a miR‐548b/FoxM1 axis

Abstract: Glioblastoma multiforme (GBM) is the most common and aggressive type of tumor of the primary nervous system. Treatment options for GBM include surgery, chemotherapy, and radiation therapy; however, the clinical outcomes are poor, with a high rate of recurrence. An increasing number of studies have shown that circular RNAs (circRNAs) serve important roles in several types of cancer. Gene Expression Omnibus (GEO) database was utilized to identify the differentially expressed cir-cRNAs and their biological functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 58 publications
(100 reference statements)
0
15
0
Order By: Relevance
“…Compared to normal tissues, FOXM1 expressed at a higher level in GBM ( Figure 3 B). A circBFAR/miR−548b/ FOXM1 axis [ 51 ] and a FOXM1 /ADAM17 feedback loop [ 52 ] have been identified as involved in the development of GBM. In this light, FOXM1 might serve as a potential target for GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to normal tissues, FOXM1 expressed at a higher level in GBM ( Figure 3 B). A circBFAR/miR−548b/ FOXM1 axis [ 51 ] and a FOXM1 /ADAM17 feedback loop [ 52 ] have been identified as involved in the development of GBM. In this light, FOXM1 might serve as a potential target for GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Co-transfection of miR-320a or forkhead box M1 (FOXM1) plasmids into glioma cells could rescue the consequences of si-circCCDC66-induced cell growth inhibition to some extent. Importantly, FOXM1 was identified as a key target of circCCDC66 involved in regulating DNA damage response pathways ( 89 ). This highlights the fact that circCCDC66 is overexpressed in gliomas and acts as an oncogene.…”
Section: Circccdc66 and Glioblastomamentioning
confidence: 99%
“…Circ_0000218 was up‐regulated in LSCC cells and negatively regulated the expression of miR‐139‐3p to promote LSCC cell viability and inhibit apoptosis 9 . Of note, previous studies suggested that circBFAR frequently acted as a carcinogenic factor by regulating cell proliferation, invasion, and glycolysis in diverse tumors 10,11 . However, the role and mechanism of circBFAR in the development of LSCC have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Of note, previous studies suggested that circBFAR frequently acted as a carcinogenic factor by regulating cell proliferation, invasion, and glycolysis in diverse tumors. 10 , 11 However, the role and mechanism of circBFAR in the development of LSCC have not been reported.…”
Section: Introductionmentioning
confidence: 99%